PHARMACOECONOMIC EVALUATION OF DABIGATRAN VS WARFARIN IN CARDIOVASCULAR EVENTS PREVENTION IN PATIENTS WITH NON-VALVULAR ATRIAL FIBRILLATION - Yu. B. Belousov; V. Yu. Mareev; I. S. Yavelov; D. Yu. Belousov (Столичная издательская компания, 2015)
According to recent guidelines, oral dabigatran etexilate is indicated for stroke and systemic embolism prevention in patients with atrial fibrillation (AF). Aim. Based on the RE-LY study to evaluate the cost-effectiveness of dabigatran etexilate versus warfarin prescribed in "real-world" settings from a Russian payer perspective. Material and methods. Markov model simulated AF patients at moderate to high risk of stroke while tracking clinical events and resulting functional disability. Acute event costs and resulting long-term follow-up costs incurred by disabled stroke survivors were calculated using general tariff agreement of Russian obligatory health insurance system and official national statistics. Clinical events, summarized as events per 100 patient-years, expected life years, total costs, and incremental cost effectiveness ratios (ICER) were calculated. Results. Over a lifetime, dabigatran etexilate treated patients experienced fewer intracranial haemorrhages and fewer ischaemic strokes. ICER of dabigatran etexilate was 461,602 roubles per one additional life year versus "real-world" warfarin. Conclusion. This study demonstrates that dabigatran etexilate is a cost-effective alternative to current care for the prevention of stroke and systemic embolism among Russian patients with AF .